Ecological Requirements In Financing Selected Power Plants In Poland - Małgorzata KOŻUCH; Renata ŻABA-NIERODA (Communications of International Proceedings, 2021)
The paper attempts to identify financial categories related to the implementation of projects aimed at attaining ecological standards. The basic ecological standards applicable to power plants are: emission reduction, specific level of energy produced from renewable sources, obtaining appropriate ecological efficiency. The report uses the financial statements of the power plant. Identification takes place at two levels: first, by identifying the size and categories included in the plant's financial statements; second, by isolating: revenues, costs, assets, capitals, revenues and expenses associated with the alignment of power plants with environmental standards.
Keywords: Ecological Standard; Power Station; Financial Statements; Outlays; Costs.